A study on the positive impact of physical education on children's mental health - Niu, Peilin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Everyone's health is highly important. Dealing with health issues is just as important as dealing with financial ones. Any country's economic survival is totally based on its own economic strategy. The primary purpose of research on the relationship between exercise and fitness, as well as its influence on economic survival, is to help us understand the value and importance of exercise and physical fitness in our lives. It is hard to refute the benefits of exercise and physical activity on one's health. The study of differences in physical fitness and activity between men and women. The independent factors in this study include exercise and physical fitness, while the dependent variable is economic survival. The data was analysed using AMOS 26v. Because there were three hypothesis statements in this research, the findings showed that the variables had a positive and significant link.